EFFECT OF NPK AND POTASSIUM NITRATE FERTILIZATION ON YIELD, OIL PERCENTAGE AND SOME CHARACTERISTICS OLIVE CULTIVAR - Ihsan A. Shaker (Mesopotamia Journal of Agriculture)
This study was carried out in a private local orchard north of Mosul, Iraq (Bashiqa area) for two growing seasons (2000- 2001) to study the effect of foliar application of potassium nitrate and NPK fertilization on the yield and oil percentage of Ashrasi olive cultivar (local variety olea europaea L.). The major results are summarized as follows: First spraying date (Autumn) was better than the second date (spring) in all characteristics namely: leaf content of nutritional elements such as nitrogen and potassium content, the dry weight of leaves, total of chlorophyll quantity, fruit set ratio fruit weight, yield. Did not differ significantly. Spraying with potassium nitrate leaf gave significant result in the content of nitrogen and potassium leaf dry weight, the total chlorophyll quantity, fruit set and fruit weight except the yield quantity which influenced with higher concentration of potassium nitrate only. Application of NPK fertilizer caused a significant increase in some characteristics such as the nutritional element content of nitrogen and potassium. Fruit weight in both concentrations the yield and fruit ratio in low concentration.